Aula invertida en el proceso de enseñanza - aprendizaje en estudiantes de séptimo grado de la Escuela Zoila Alvarado de Jaramillo - Sánchez Rivera, Marisol Alexandra (2022)
It is essential to know that inverted classroom is a methodology that develops cognitive skills in students that encompasses enhancing critical and analytical thinking of students, while allowing autonomy in their activities and carrying out in addition to building significant knowledge; In this case, the methodology is a primary factor in the study processes. To comply with the proposed objectives, emphasis has been placed on the search for information for the development of the theoretical framework, in the case of the two specific objectives, the necessary guidance has been provided so that the research can be carried out with relevant characteristics, and in The third specific objective has developed a didactic guide that will allow the institution to know and apply the flipped classroom. The research is based on a mixed approach, in which various research methods were involved such as: deductive, analytical, synthetic, scientific and statistical that allowed the analysis of the information collected, data collection instruments were also used such as the interview and the poll. Once the information obtained at the Zoila Alvarado de Jaramillo Basic Education School in the city of Loja was analyzed, it was found that the current form of teaching by the teacher requires external support, which facilitates the cognitive development of the students; since its use improves the understanding of lasting and significant contents, the use of technological and interactive tools, also allows changing the structure of a passive education for an active one, linking with the strengthening of new positive activities in front of the study. Keywords: Significant learning, active methodology, technological tools, learning, study.